IoT Monitoring Suhu dan Kelembaban Udara dengan Node MCU ESP8266 - Beni Satria (sudo Jurnal Teknik Informatika, 2022)
Currently the demand for automation and intelligence systems is very high. That's why people are showing interest in smart devices. For example, people can control or monitor their household appliances via the web or applications via mobile phones. Internet of Things (IoT), which can make these devices or hardware devices communicate, exchange data, and control each other via the web or smartphone applications. Temperature and humidity in the environment can also be monitored via the web and smartphones using (IoT) so that the air in the environment remains healthy and awake. In this study, the ESP8266 MCU Node and the DHT11 sensor were used which can measure temperature and relative humidity. The IoT platform used is Blynk which is connected to a smart phone. The results of this study are temperature and relative humidity readings that can be monitored in real time via a smart phone, making it very easy for our efforts to monitor temperature and humidity in a place